2015
DOI: 10.1007/s11356-015-4177-4
|View full text |Cite
|
Sign up to set email alerts
|

Morphological alterations in the liver of yellow perch (Perca flavescens) from a biological mercury hotspot

Abstract: Mercury (Hg) contamination is a global issue due to its anthropogenic release, long-range transport, and deposition in remote areas. In Kejimkujik National Park and National Historic Site, Nova Scotia, Canada, high concentrations of total mercury (THg) were found in tissues of yellow perch (Perca flavescens). The aim of this study was to evaluate a possible relationship between THg concentrations and the morphology of perch liver as a main site of metal storage and toxicity. Yellow perch were sampled from five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Accordingly, Villegas et al detected Hg via electron microscopy deposits in neurosecretory neurons of mice after long term oral exposure to HgC1 2 in drinking water exclusively within lysosomes [39). Additionally, accumulation of Hg in hepatic lysosomes was reported for yellow perch, sampled in a Canadian region known as a biological mercury hotspot (40), and for rainbow trout fed with a MeHg supplemented feed diet for 7 weeks [ 41).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, Villegas et al detected Hg via electron microscopy deposits in neurosecretory neurons of mice after long term oral exposure to HgC1 2 in drinking water exclusively within lysosomes [39). Additionally, accumulation of Hg in hepatic lysosomes was reported for yellow perch, sampled in a Canadian region known as a biological mercury hotspot (40), and for rainbow trout fed with a MeHg supplemented feed diet for 7 weeks [ 41).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, biological effects assessed with the IBR index (it included six parameters in flounder and eight parameters in mussels), presented in the form of star plots, indicated that in flounder, it was not the high EROD activity but the MMA density in liver and spleen that showed the greatest relative degree of response and distinguished the three contaminated sites from the reference site. The utility of MMA as a biomarker of contaminant exposure and/or fish health has been demonstrated in several other studies (Fournie et al 2001;Müller et al 2015;Patiño et al 2003;Schwindt et al 2008). According to Wolke (1992), the functions of MMAs are multiple and complex including immune and inflammatory responses as well as storage and destruction or detoxification of various substances.…”
Section: Discussionmentioning
confidence: 92%
“…A further study on metal toxicity was carried out with yellow perch, Perca flavescens, from mercury-contaminated lakes in Canada (Müller et al 2015). The study showed a clear relation between a specific cellular reaction in the liver-the formation of macrophage aggregates-and the level of mercury burdens in the fish.…”
Section: This Special Issue Of Environmental Science and Pollutionmentioning
confidence: 99%
“…behaviour) of the aquatic organisms. Thus, the former view that only apical responses are responsible for changes in population growth and survival has shifted towards the understanding that also subtle toxicant effects can have ecological relevance (Relyea and Hoverman, 2006). This may be particularly relevant for chemicals with specific modes of action (e.g.…”
Section: This Special Issue Of Environmental Science and Pollutionmentioning
confidence: 99%
See 1 more Smart Citation